Factors related to college students’ decisions to report sexual assault - Spencer, Chelsea Marie (Kansas State University, 2016)
Sexual assault is a serious problem on college campuses. The purpose of this study was to examine factors that are associated with sexual assault survivors reporting their assault. The sample included 266 individuals who had experienced a sexual assault since enrolling in their university. A multinomial regression was tested to predict the odds of whether or not the survivor made a formal report of the assault, an informal report to friends or family members, or if the survivor told no one about the assault. The type of assault, the survivor’s relationship to the perpetrator, whether or not the survivor was drinking alcohol at the time of the assault, whether or not the survivor received sexual assault training, and the survivor’s perception of the overall campus climate were added as predictors of the odds of making a report. The participant’s belief that the university would handle the assault appropriately was used as a moderator of those associations. Race/ethnicity, gender, and sexual orientation were used as control variables. It was found that if the survivor had received sexual assault training, if the assault was vaginal or anal sex, and if the survivor had a positive perception of the overall campus climate, they were more likely to formally report the assault. If the perpetrator was an acquaintance, friend, or dating partner, survivors were less likely to formally report the assault. If the survivor was a racial or ethnic minority, they were less likely to formally or informally report the assault. Our findings suggest that there are ways universities can aid in survivors reporting their sexual assault through education, training, and improving the overall campus climate.
Keywords: sexual assault; college campuses; sexual violence; reporting behaviors